Daytime tweek atmospherics. Issue 1 (8th January 2015) - Ohya, Hiroyo; Shiokawa, Kazuo; Miyoshi, Yoshizumi
Abstract We report the first observation of daytime tweek atmospherics based on measurements at Moshiri (44.37°N, 142.27°E) and Kagoshima (31.48°N, 130.72°E), Japan, during nonsolar eclipse days for 5 months in 1980–1994. The daytime tweeks were observed on geomagnetically quiet and stormy days. The daytime tweeks had clear frequency dispersion with an average duration of 12 ms, which was shorter than that in the nighttime ( 50 ms). The average occurrences of the daytime tweeks at Moshiri and Kagoshima were 0.6 and 0.1 tweeks per minute during 10:00–15:00 LT, respectively. Daytime tweeks up to the second‐order mode were visible. There was no difference in the occurrence of each visible mode between storm time and magnetically quiet time. The daytime reflection heights were similar to those at night (85–100 km) but with greater variation. We evaluated the attenuation rate (αn) of tweeks by strictly taking the ionospheric reflection coefficient into account. For each frequency, αn was evaluated as a function of the electron density, electron density gradient, and ionospheric height. We found that αn had an inverse relationship with the electron density (or conductivity), electron density gradient, and ionospheric height. We suggest that the best conditions for daytime tweek observations are when the bottomside of the ionosphere is sharply defined and the ionospheric height is high.